Research on the Stability of the Banking System With Shadow Banking Under Macroeconomic Fluctuation - Pan, Hongjie; Fan, Hong (Frontiers in Physics, 2020)
In recent years, shadow banking is considered to be one of the important factors that cause the financial crisis and destroy the stability of the banking system. However, in fact, macroeconomic fluctuations are closely related to the stability of the banking system. As an indispensable part of the decision-making of shadow banking, the shock of macroeconomic fluctuations plays a vital role as well. Therefore, based on the agent-based method in modern complex network theory, a model of a dynamic complex interbank network with shadow banking under macroeconomic fluctuations is proposed in this paper, in which the shock of macroeconomic fluctuations on the stability of the banking system with shadow banking and the effect of the shadow banking on the macroeconomic fluctuation are explored. The results show that in the boom, the liquidity of the banking system is expanded, the average bank profits are improved, the investment opportunities are increased, the survival bank ratio is high, and the systemic risk is low. The banking system stability is increased. While in the stable and the bust, the liquidity of the banking system is declined, average bank profits are shrunk, investment opportunities are gradually disappeared, and the survival bank ratio is decreased. The shadow banking starts collapsing, the systemic risk breaks out, and the banking system stability is seriously damaged. Furthermore, by analyzing the influence of shadow banking on the macroeconomic fluctuations, we find that shadow banking builds up the fragility of macroeconomic performance and without external regulation this impact is irreversible. This paper sheds light on the impact of macroeconomic fluctuation on the stability of the banking system with shadow banking, shows the risk problems brought by shadow banking for economic fluctuation, refines research of the banking system stability, and offers effective theoretical references for decision-makers and regulators.